Child Heritage Language Development: An Interplay Between Cross-Linguistic Influence and Language-External Factors - Meir, Natalia; Janssen, Bibi (Frontiers in Psychology, 2021)
The current study investigated the mechanisms of Heritage Language (HL) development with a focus on case morphology. First, it assessed the effects of cross-linguistic influence (i.e., the influence of the properties of the Societal Language (SL) on the acquisition of the HL) by performing bilingual-vs.-monolingual, and between-bilingual, group comparisons (Russian-Dutch vs. Russian-Hebrew bilinguals). Russian, Hebrew, and Dutch show differences in the marking of accusative (ACC) and genitive (GEN) cases, and these differences were used as a basis for the evaluation of cross-linguistic influence. Second, the study evaluated the contribution of language-external factors, such as chronological age, age of onset of bilingualism (AoO), languages spoken by the parent to the child (only HL, only SL, both HL and SL), and family language type (both parents HL speakers, mixed families). Finally, we assessed how language-external factors might potentially mitigate the effects of cross-linguistic influence in bilinguals. Russian-Dutch bilinguals from the Netherlands (n=39, MAGE=5;1, SD=0;8), Russian-Hebrew bilinguals from Israel (n=36, MAGE=4;9, SD=0;9) and monolingual Russian-speaking children (n=41, MAGE=4;8, SD=0;8), along with adult controls residing in the Russian Federation, participated. The case production of ACC and GEN cases was evaluated using elicitation tasks. For bilinguals, background data on individual language-external factors was elicited from the participants. The results show that case morphology is challenging under HL acquisition - case acquisition in the HL is impeded under the influence of the properties of the SL. This is evident in the lower performance of both bilingual groups, compared to monolingual controls who show ceiling performance in the production of target inflection in ACC and GEN contexts. More specifically, the acquisition of morphology is hindered when there are differences in the mapping of functional features (such as with Russian-Hebrew bilinguals) and/or the absence of this feature marking (such as with Russian-Dutch bilinguals). But the findings also point to the involvement of language-external factors as important mitigators of potential negative effects of cross-linguistic influence. In summary, HL development is an intricate interplay between cross-linguistic influence and language-external factors.